1999
DOI: 10.1046/j.1526-100x.1999.72022.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Isolated Trees in Facilitating Tree Seedling Recruitment at a Degraded Sub‐Tropical Rainforest Site

Abstract: Successional development at abandoned farmlands in southern Queensland, formerly occupied by sub‐tropical rain forest is centred around scattered, isolated trees. Soil seed banks contain few woody plants and most tree species appear to be recruited from seed dispersed into the site by birds or bats. Scattered, low‐growing trees <3 m in height act as the initial focus for the activities of seed‐dispersing birds, but this process is accelerated by the development of taller trees> 6 m in height that act as bird p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 27 publications
3
88
0
6
Order By: Relevance
“…Some bird and bat species move over and into open areas, where they deposit seeds mostly, but not exclusively, beneath isolated trees or other emergent structures (Duncan & Chapman 2002;Slocum & Horvitz 2000). Because abiotic conditions for seedling regeneration are better under isolated trees (Toh et al 1999), relatively high seed deposition in these areas can also be considered directed dispersal.…”
Section: Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some bird and bat species move over and into open areas, where they deposit seeds mostly, but not exclusively, beneath isolated trees or other emergent structures (Duncan & Chapman 2002;Slocum & Horvitz 2000). Because abiotic conditions for seedling regeneration are better under isolated trees (Toh et al 1999), relatively high seed deposition in these areas can also be considered directed dispersal.…”
Section: Patternsmentioning
confidence: 99%
“…Studies have shown that seed rain is much greater beneath emergent structures such as isolated trees and snags (Duncan & Chapman 2002;Slocum & Horvitz 2000), because birds and bats are more likely to visit there (da Silva et al 1996). Seedling densities and diversities also tend to be higher in these areas (Toh et al 1999). This suggests that planting trees or adding artificial perches or other structures could enhance tree seed input and thus forest regeneration in degraded tropical areas, just as they do in some temperate systems (McClanahan & Wolfe 1993).…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute this result at least partly to the perch effect, which leads to increased seed deposition by frugivorous birds because (1) most seedlings recorded at the edges of rocky outcrops and beneath E. crispa had characteristics associated with dispersal by birds (Table 1), and (2) it is known that tall structures receive more seed rain from bird-dispersed plant species than do short ones (Holl 1998, Toh et al 1999). For instance, Toh et al (1999) found that bird-dispersed seeds were more abundant under artificial perches that were 6 m tall than under 3 m tall perches.…”
Section: Discussionmentioning
confidence: 99%
“…The use of living trees, which are characterized as natural roosts, is also an efficient strategy in recruitment of seeds and seedling establishment (VIEIRA et al, 1994;TOH et al, 1999;CARRIÈRE et al, 2002) and can contribute to the restoration of degraded areas.…”
Section: Artificial Roosts Versus Natural Roostsmentioning
confidence: 99%